Comparative assessment of conventional and light-curable fluoride varnish in the prevention of enamel demineralization during fixed appliance therapy: a split-mouth randomized controlled trial. (13th May 2017) - Shah, Mandar; Paramshivam, Ganesh; Mehta, Anurag; Singh, Surjit; Chugh, Ankita; Prashar, Anil; Chugh, Vinay Kumar
Summary: Objective: To evaluate the effects of single application of a conventional versus light-curable fluoride varnish (LCFV) on prevention of enamel demineralization during fixed orthodontic treatment over a 4 month period. Design: The research was designed as a split-mouth, randomized control trial (RCT). Methods: Twenty-two patients requiring fixed orthodontic treatment with premolar extractions were included in the RCT. In each patient, two diagonal quadrants (i.e. upper right and lower left, or vice versa) were randomly assigned to receive conventional fluoride varnish or LCFV. After allocation of one intervention, the other diagonal quadrants received the second intervention. At specific time intervals, premolars were extracted and sectioned, and the demineralized lesion was assessed in each group. Main outcome measures: The primary outcome was demineralized enamel lesion depth (DELD) at the end of 45, 90, and 120 days. Randomization: A simple complete randomization list using random allocation rule (restricted randomization) was computer generated to ensure homogeneity of application of conventional or LCFV to each contralateral quadrant in a split-mouth design. Allocation concealment was not employed. Blinding: Blinding was done only for outcome assessor because of clinical limitations. Results: Twenty-two patients with 88 teeth were enrolled in the trial. After excluding the drop-outs, primary analysis was performed on 66 teeth distributed among two interventional groups. Mean difference between DELD among two groups was 36.6 µm [95 per cent confidence interval (CI) 34.61–38.55] and 58.5 µm [95 per cent confidence interval (CI) 55.65–61.43] at 90 and 120 days, respectively. Cluster level analysis performed by Paired t -test showed that DELD was significantly higher ( P < 0.001) in the conventional fluoride varnish group at the end of 90 and 120 days as compared to LCFV group. No adverse effect was observed in any patient. Limitations: Being a histologic study, the role of fluoride varnish could be assessed only for 4 months. Conclusion: The result of this study indicate that single application of LCFV (Clinpro™ XT) can prevent enamel demineralization for longer duration (for up to 4 months) of time as compared to conventional fluoride varnish (Duraphat™, 45 days) during fixed appliance therapy. Registration: The trial was registered retrospectively in the Clinical Trial Registry-India, number CTRI/2016/09/007232.